Nonfiction as Queer Aesthetic: Score for Five Speakers in Two Acts - Francesca Rendle-Short; Quinn Eades; Barrie Borich; Peta Murray; Lawrence Ypil (2018)
BACKGROUND: What if, as Barrie Jean Borich asks, all nonfiction writers imagined a queer aesthetic at the center of our discourse (2012)? What might this imaginary look like, feel like? This is a nonfiction that, as Borich dreams it, is 'attentive to form but difficult to classify, with quirky yet intentionally designed exteriors, slippery rules'. This creative work, co-authored and shared equally among the five contributors, embraces the imagined space of the queer aesthetic head on. CONTRIBUTION 'Nonfiction as Queer Aesthetic: Score for Five Speakers in Two Acts' brings together a culturally diverse group of writers to explore the idea of the queer aesthetic as it relates to nonfiction writing and our community of practice. It asserts the idea that genre, like gender, is not so much passé, as Kazim Ali suggests (2013), but that it is boring. This creative score-as-essay goes beyond genre; it nudges, explodes, queries, transgresses, dreams, confesses, upholds, sews together, slides, dances, essays. It puts the body centre stage and allows it to move and perform as it sees fit, paying attention to what and how things are said and/or not said (content and form coalescing). SIGNIFICANCE 'Nonfiction as Queer Aesthetic' was presented at the NonfictioNOW Conference in Reyjkavik, Iceland in June 2017. NonfictioNOW is the world's leading biennial gathering in the field of nonfiction creative writing. Over 400 international writer/scholars attend the biennial conference established in 2005 at the University of Iowa (ranked #1 in the USA in Creative Writing). All panels proposed to the conference undergo a highly competitive review process. The editor of Fourth Genre heard the panel in person and invited the presenters to submit this performed work to the journal, reimagined as a work for the page. Fourth Genre is published biannually by the Michigan State University Press, a journal devoted to publishing notable, innovative work in nonfiction, one that explores the markers and boundaries of literary/creative nonfiction.